Spirometry in Diffuse Parenchymal Lung Diseases - Mohanty, Dr. L. K.; Vachhani, Dr. Rashim (International Journal of Innovative Research in Medical Science, 2018)
A total 45cases diagnosed to have diffuse parenchymal lung disease were taken for study and compared with 70 normal control subjects. The mean age of presentation of diffuse parenchymal lung disease (ILD) was 50.15 + 13.16 years. Male Female ration were 1.6:1 the commonest presenting symptoms are breathlessness and commonest clinical sign was file mid to late in respiratory crackles. A significant reduction (P<0.05) in mean value of FVC, FEU, FEF 25-75% PEF and MVU has been obtained in ILD in compared with normal controls. The mean value of FEV1/FVC (%) has been observed slightly raised in ILD cases compared with normal. The apparent difference was statistically non significant (P>0.05). The commonest venltilatory defect observed in ILD cases restrictive defect.